Gas gangrene A patient’s history from an OR nurse’s perspective Part 2 - Aboud, Diane; Williams, Jan (Operating Room Nurses Association of Canada Journal, 1991)
Recently, at the Riverside Hospital in Ottawa, an active treatment community hospital of 274 beds, the operating room encountered a case of gas gangrene in a young female patient. The case touched the entire operating room nursing staff, most of whom are mothers with teenage daughters. We were all shaken by the fact that the patient was also in her teens.